Tinjauan Geografis "Litoralisasi" di Kawasan Pesisir Selatan Yogyakarta - T Triyono (Forum Geografi, 2009)
"Littoralization" can be geographically studied based on geomorphological approach and landuse system. The method of coastal geography provides useful data of geomorphology and landuse system. This research was conducted in the coastal area of south of Yogyakarta. To process spatial data was used Geographic Information System (GIS) methods (i.e. Aerial photography, satellite imagery, and field observation results). The results showed that the research area has a volcanic sandy coastal typology with flat to sloping topography. Further, this typology is divided into three units of typology, the active beach ridge and sand dunes, non-active beach ridge, and the foot hills. Development of the settlements tends toward the sea due to economic dependence on beach tourism.